I hvilken grad kan gruppeveiledning være et middel til å forebygge sykefravær på et sykehjem? - Gunnar Vold Hansen (Septentrio Academic Publishing, 2014)
This article analyzes the experience of applying group supervision in a nursing home in order to reduce sick leave. Data were collected by interviewing participants from three different groups and the counseling supervisor. The study shows that group counseling may reduce some of the risk factors leading to sick leave, but this requires that both the supervision and the group, serves as a resource for employees who feel that they have a demanding job